The Role of Student Services in Improving Student Learning in Higher Education in Cambodia - Chantrea, Moeurn (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
The Royal Government of Cambodia envisions transforming the country into a middle-income nation by 2030 and a developed nation by 2050, focusing on building human capital to foster a knowledge-based society. As a result, Cambodia's number of higher education institutions (HEIs) has grown significantly over the past decade. Notably, student services have been identified as the fifth criterion to ensure that Cambodian higher education meets regional and global standards. However, up to now, there has been much research focused on student services in Cambodia HEIs. This study, therefore, strives to fill this gap by identifying the benefits of student services in Cambodia's higher education sector. This study explores the impact of student services on student learning outcomes in higher education in Cambodia, an area that has received limited attention from researchers and relevant education sectors. Using a qualitative approach, purposive sampling was used to conduct semi-structured interviews with 38 key informants from various institutions. The interviews included face-to-face discussions with key informants and focus group discussions with students. The research identified four main benefits of student services: academic development, personal development, career development, and citizenship development. The findings suggest that enhancing student service quality is essential for HEIs to create a supportive environment that promotes student learning and ensures overall HEI quality. Key recommendations are given for policymakers and HEI stakeholders in Cambodia based on the findings, particularly the potential advantages for HEIs in using student services to guarantee their financial stability and greater quality of education.